Conservation Effort of Natural Enemies Animal by Creating The Green Park and Play Ground in Malang - Lubna Ahmed Abo Al-Qassem Shahub; Bagyo Yanuwiadi; Zaenal Fanani (Graduate Program, 2017)
The play grounds and green parks in Malang was developed until nowadays in the effort of enhancement the environment in Malang. With improving of the quality of services of that public area, it will increase the achievement of visitor satisfaction and their perception about its function. The research was conducted to evaluate the existing condition in Malang City Park, to analyze the perception of the visitors to the utilization play grounds in the city and to formulate the recommendations in improving the play ground for the conservation of natural enemies. For these purposes, questionnaires were developed and it was interviewed to the visitors of the play ground as respondents. Data collected were analyzed using Gap Analysis compared to the ideal of green park as play ground according to the governance criteria. Based on research results, most of the visitors were satisfy with the play ground, but their perception to its function were no so clear. By implementing some suggestion of the stakeholders (University and Non-Governmental Organization) almost all of the criteria of ideal green open space were already similar with its from the government. The improvement in the educational characters of the play ground and be considered for the ideal multifunction play ground in Malang City.Keywords: multi function, play ground, visitor perception